Hubungan Umur dengan Faktor-Faktor Kesehatan Gigi dan Mulut di Kalangan Masyarakat di Kecamatan Tayan Hilir Kabupaten Sanggau Tahun 2025 - Rusmali, Rusmali; Herlina, Rita; Mahmiyah, Erma (LPPM Institut Pendidikan Nusantara Global, 2025)
The province of West Kalimantan has an area of 146,807 km² with an individual DMF-T Index of 6.2, meaning that on average its population experiences 6–7 dental health problems such as cavities, teeth extracted due to caries, and previously filled teeth that remain in good condition (West Kalimantan Provincial Health Office, 2017). In Sanggau Regency, based on the 2018 Basic Health Research (Riskesdas), 48.43% of the population experienced cavities/toothache, 23.73% had teeth extracted or lost on their own, only 3.0% received dental fillings, and 12.75% had loose teeth. Research by Rusmali et al. (2023) reported the following findings: OHI-s status 15.7%, toothbrushing behavior 15%, and the influence of dental and oral hygiene on age at 21.3%, with significance values of 0.032 < 0.05 and 0.00 < 0.05. This study aimed to describe and analyze the relationship between age and dental and oral health factors among the community in Tayan Hilir District, Sanggau Regency, in 2025, using quantitative and qualitative methods, random sampling, survey sheets and questionnaires, and univariate, bivariate, and multivariate analyses with Regression and Correlation tests. The results showed that 59.4% of respondents brushed their teeth twice a day, the average dental and oral hygiene status (OHI-s) was moderate at 53.8%, the R value (0.168) approached 1, and R² (0.23) indicated that age accounted for 23% of the variation in dental health factors. The study concluded that the relationship between age and dental health factors was 23%, indicating a strong correlation.